QARAQALPAQ PROZASÍNDA DETEKTIV GÚRRIŃLERDIŃ TUTQAN ORNÍ (J.Óteniyazovtıń detektiv gúrrińleri mısalında) - Allamuratova, Z.M. (НАУКА и ОБЩЕСТВО, 2023)
The article discusses the use of detective forms in the stories of J. Uteniyazov. The essence of detective stories in Karakalpak literature is studied in detail and expressed with examples.